Application of integrative physiological approach to evaluate human physiological responses to the inhalation of essential oils of Japanese citrus fruits iyokan (Citrus iyo) and yuzu (Citrus junos). Issue 1 (8th November 2021) - Ohata, Motoko; Zhou, Lanxi; Ando, Shiori; Kaneko, Shu; Osada, Kazumi; Yada, Yukihiro
ABSTRACT: This study investigated the effects of essential oil odors from Japanese citrus fruits, iyokan ( Citrus iyo ) and yuzu ( Citrus junos ), on human psychology and both the autonomic and central nervous systems. The inhalation of both essential oils significantly increased miosis rate and fingertip temperature and could induce parasympathetic dominance by suppressing sympathetic nerve activity. Oxyhemoglobin concentration in the prefrontal cortex increased after the inhalation of yuzu essential oil and decreased after the inhalation of iyokan essential oil. Subjectively, the inhalation of both essential oils reduced the feelings of fatigue and improved the feelings of refreshment, suggesting that the effect of autonomic nervous activity might involve in these psychological changes directly. Moreover, we observed that task performance improved after inhaling yuzu essential oil, which may be due to the increase in oxyhemoglobin concentration in the prefrontal cortex. Graphical Abstract: